Assessment of Tourism Infrastructure in Pokhara and Its Efficacy as Tourism Capital of Nepal - Malla , Subash (KIC International Journal of Social Science and Management, 2024)
Pokhara is the pioneer and prominent player of Nepalese tourism industry with stunning scenery, clement climate and smiling souls. Nearly half of the total international visitors and more than two-third of the total trekkers visit Pokhara every year. An exploratory study was done to assess the tourism infrastructure of Pokhara using qualitative data from nine key informant experts. These experts were purposively selected from diverse field having at least dozen years of experience. The study finds that Pokhara has natural beauty, cultural uniqueness, adventure sports, good hotels & restaurants and recreation means. Still, it needs to improve its accessibility related physical infrastructures as well as some service infrastructures to be well established as the best destination in the country. On the same mirror, announcement of Pokhara as Tourism Capital of Nepal seems to be a bit hurried publicity stunt. The policy makers should strongly show their commitment on developing tourism infrastructures before any other new announcements.